2018
DOI: 10.1101/282426
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal Control of Transcription by Zelda in living Drosophila embryos

Abstract: Abstract/introPioneer factors have the exquisite ability to engage their target sites at nucleosomal DNA, which leads to a local remodeling of chromatin and the establishment of a transcriptional competence. However, the direct impact of enhancer priming by pioneer factors on the temporal control of gene expression and on mitotic memory remains elusive. In Drosophila embryos, the maternally deposited activator Zelda (Zld) exhibits key pioneer factor properties and indeed regulates the awakening of the zygotic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 33 publications
(58 reference statements)
3
10
0
Order By: Relevance
“…Based on previous observations (Hannon, Blythe, and Wieschaus 2017) that Bcd binding in more posterior nuclei is dependent on Zld, we examined the distribution of Bcd binding in nuclei lacking Zld and found that Bcd hubs no longer form ) . Our preliminary experiments with fluorescently tagged Zld revealed that it also forms hubs (distinct clusters of Zld were also recently reported by (Dufourt et al 2018) ).…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Based on previous observations (Hannon, Blythe, and Wieschaus 2017) that Bcd binding in more posterior nuclei is dependent on Zld, we examined the distribution of Bcd binding in nuclei lacking Zld and found that Bcd hubs no longer form ) . Our preliminary experiments with fluorescently tagged Zld revealed that it also forms hubs (distinct clusters of Zld were also recently reported by (Dufourt et al 2018) ).…”
Section: Introductionsupporting
confidence: 80%
“…Recently, a highly clustered spatial distribution of Zld was reported using confocal microscopy (Dufourt et al 2018) , but the temporal dynamics of these clusters have not been examined due to the technical limitations of confocal microscopy. We thus performed high resolution 4D imaging using LLSM of Zld in developing embryos.…”
Section: Zelda and Bcd Form Dynamic Subnuclear Hubsmentioning
confidence: 99%
“…So far, clear evidences of passive supports of memory are lacking. In a recent work, by monitoring transcriptional activation in living early Drosophila embryos, it was shown that experiencing transcription prior to mitosis does not always lead to a rapid post-mitotic activation [11] . With a mesodermal enhancer, memory of active transcriptional states is unequivocally occurring [12] , while with a dorsal ectoderm enhancer, memory is not detected [11] .…”
Section: Mitotic Bookmarking and Developmentmentioning
confidence: 99%
“…However, little is known regarding the functional importance of pioneer factors for mitotic memory in developing multicellular organisms. Intriguingly, the pioneer factor Zelda, an essential activator of the early zygotic genome in Drosophila embryos, is not retained during mitosis and does not contribute to mitotic memory [11] . This could reflect that mitotic bookmarking is not a general feature of all pioneer factors, or alternatively, that Zelda is not a canonical pioneer factor.…”
Section: Mitotic Bookmarking and Developmentmentioning
confidence: 99%
See 1 more Smart Citation